REKONSTRUKSI TIME VALUE OF MONEY MENUJU ECONOMIC VALUE OF MONEY UNTUK KEUANGAN ISLAM - Muhamad . (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2012)
As the cornerstone of conventional financial system, Time Value of Money (TVM) is quite differ from the Islamic financial system, because the existing element of Riba. On this basis, it is necessary for the Muslim economist to rectify those concepts by proposing the concept of Economic Value System (EVT) that is how someone utilizes the time. The increase of money value is determined by the economic activity and not by the course of time. Therefore, the economic actors should utilize the time and optimize the economic activities as to obtain the value added requirements. The economic value added in Islamic financial system is the result of return, ratio, velocity and capital.